2014
DOI: 10.1128/cvi.00138-14
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni Soluble Egg Antigens Enhance Listeria monocytogenes Vector HIV-1 Vaccine Induction of Cytotoxic T Cells

Abstract: Vaccines are an important public health measure for prevention and treatment of diseases. In addition to the vaccine immunogen, many vaccines incorporate adjuvants to stimulate the recipient's immune system and enhance vaccine-specific responses. While vaccine development has advanced from attenuated organism to recombinant protein or use of plasmid DNA, the development of new adjuvants that safely increase immune responses has not kept pace. Previous studies have shown that the complex mixture of molecules th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Evaluation of the influence of SEA on the generation of CD4 ϩ and CD8 ϩ T cell responses of Lm-Gag-vaccinated C57BL/6 mice demonstrated that similar to our recent study (24), the administration of SEA with Lm-Gag significantly increased the level of Gag-specific CTL effectors compared to those in mice vaccinated with Lm-Gag alone (Fig. 3D).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Evaluation of the influence of SEA on the generation of CD4 ϩ and CD8 ϩ T cell responses of Lm-Gag-vaccinated C57BL/6 mice demonstrated that similar to our recent study (24), the administration of SEA with Lm-Gag significantly increased the level of Gag-specific CTL effectors compared to those in mice vaccinated with Lm-Gag alone (Fig. 3D).…”
Section: Discussionsupporting
confidence: 62%
“…Together, the results presented here and in our recent study (24) show that SEA functioned counterintuitively when administered with the Lm-Gag vaccine, stimulating CTL responses rather than suppressing them. Although it is well known that Listeria is a potent inducer of CD8 ϩ immunity, the specific mechanism(s) by which Listeria vector vaccines can both overcome the immunosuppressive environment of chronic helminth infection (12,13) as well as be adjuvanted by SEA is currently being investigated.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The high levels of IFNγ observed would play a role in stimulating the B cells to produce IgG [49] which is important for effective HPV vaccine responses [51]. There is also evidence that SEA from the eggs released during a S. mansoni infection also stimulated the production of proinflammatory cytokines [52]. The findings of this study indicates that a chronic S. mansoni infection or previous exposure to schistosomiasis does not down-regulate Th1 cellular responses to HPV Vaccine.…”
Section: Chronic S Mansoni Infection Has No Significant Effect On Cymentioning
confidence: 79%
“…The burden of cervical cancer in Sub-Saharan Africa has been steadily increasing and this had led to the introduction and testing of HPV vaccines in Africa [2][3][4][5][6]. Currently, three licensed vaccines against HPV are available; the quadrivalent vaccine Gardasil which provides protection against HPV 6,11,16,18, bivalent vaccine Cervarix which confers protection against the 2 variants, HPV 16 and HPV 18 [7] and a nanovalent vaccine Gardasil9 which protects against HPV 16,18,31,33,45,52 and 58 subtypes [8,9]. These vaccines contain virus-like-particles (VLPs) consisting of the L1 capsid protein.…”
Section: Introductionmentioning
confidence: 99%